Involvement of the interleukin 2 pathway in the rearrangement and expression of both alpha/beta and gamma/delta T cell receptor genes in human T cell precursors (The Rockefeller University Press, 1988)
In this report, we have undertaken the phenotypic, functional and molecular characterization of a minor (less than 5%) subpopulation of adult thymocytes regarded as the earliest intrathymic T-cell precursors. Pro-T cells were immunoselected and shown to express different hematopoietic cell markers (CD45, CD38, CD7, CD5) and some activation-related molecules (4F2, Tr, HLA class II), but lack conventional T cell antigens (CD2-1-3-4-8-). TCR-gamma RNA messages are already expressed at this early ontogenic stage, while alpha and beta chain TCR genes remain in germline configuration. In vitro analyses of the growth requirements of pro-T cells demonstrated the involvement of the IL-2 pathway in promoting their proliferation and differentiation into CD3+ CD4+ or CD8+ mature thymocytes. Moreover, during the IL-2- mediated maturation process rearrangements and expression of both alpha and beta chain TCR genes occurred, and resulted in the acquisition of alpha/beta as well as gamma/delta (either disulphide-linked or non- disulphide-linked) heterodimeric TCR among the pro-T cell progeny.